Oxytetracycline excretion in sows' colostrum and milk - Fernández Paggi, María Belén (2018)
In intensive pig farming antibiotics are often administered to sows during peripartum for the treatment of mastitis metritis agalactea (MMA) on one hand and with the irrational goal of decreasing the bacterial load to which new born piglets would be exposed. The passage of antibiotics to colostrum and milk that could affect intestinal health of the litter is not taken into account when these treatments are implemented. The aim of this study was to assess colostral and milk elimination in sows after the treatment with oxytetracyline solution (OTC-S) and long acting oxytetracycline (OTC-LA) during peripartum.